Analysis of Determination in Computer-Based Information Systems: The Role of Databases, Computer Networks, and Technological Innovation - Isnawati, Isnawati; Ali, Hapzi (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
Analysis of the Determinants of Computer-Based Information Systems: The Role of Databases, Computer Networks, and Technological Innovation is an analysis of the works that have been published in the subject of ESSB. In order to provide a basis for future research, this article aims to generate hypotheses about the correlation between variables. Academic databases such as Google Scholar, Mendeley, and others are part of the research object. This research utilizes a literature review strategy based on the use of publicly accessible electronic resources, such as e-books and journals. Descriptive qualitative analysis was used. The following are the findings of this analysis: 1) The Role of Database in Determination Analysis of Computer-Based Information System; 2) The Role of Computer Networks in the Determinacy Analysis of Computer-Based Information Systems; 3) The Role of Technological Innovation in the Determination Analysis of Computer-Based Information Systems.